Association between rTMS-induced changes in inflammatory markers and improvement in psychiatric diseases: a systematic review - Pedraz Petrozzi, Bruno; Insan, Shrabon; Spangemacher, Moritz; Reinwald, Jonathan Rochus; Lamadé, Eva; Gilles, Maria; Deuschle, Michael; Sartorius, Alexander (Annals of general psychiatry, 2024)
Background: Repetitive transcranial magnetic stimulation (rTMS) has recently gained relevance in treating different psychiatric disorders. Limited evidence suggests that the beneficial effects of rTMS on psychopathology could be at least partly mediated through changes in inflammatory response. This systematic review summarizes the literature on whether rTMS can modulate inflammatory markers and thus positively influence the course of psychiatric illnesses. Materials and methods: A systematic review of rTMS and inflammatory markers in psychiatric diseases was conducted according to PRISMA guidelines. Information on the association between rTMS treatment response and changes of inflammatory markers was extracted. The quality of the studies was assessed using the National Heart, Lung, and Blood Institute for human studies and the Systematic Review Center for Laboratory Animal Experimentation for animal studies. Results: This review includes 17 studies (2 animal and 15 human studies) on the relationship between rTMS treatment response and changes of inflammatory markers. Positive changes in microglial activity and anti-inflammatory effects were associated with behavioral improvement in animal models of depression. However, these findings have not been consistently replicated in human studies focusing on treatment-resistant depression. While several studies reported rTMS-induced alterations in peripheral inflammatory markers, only two could demonstrate their association to clinical treatment response. Notably, most studies showed poor or moderate quality in the bias assessment. Conclusions: While certain human studies suggest an association between rTMS-induced anti-inflammatory effects and improvement in psychopathology, heterogeneity, and underpowered analyses constrain the generalizability of these results. The discrepancy between animal and human findings highlights the need for larger, standardized human studies. Trial registration: (PROSPERO Registration: CRD42023492732).
Gesehen am 30.09.2024